Ethnobotanical Study of Tea Plants Based on Local Wisdom in Ngargoyoso District, Karanganyar Regency, Central Java - Hapsari, Kharisma Margiyana Dinda; Roziaty, Efri (Universitas Muhammadiyah Surakarta, 2023)
Ethnobotany is the relationship between humans and natural resources to meet needs such as food, medicines, traditional ceremonies, and other community life. Tea plants are plants that have a high selling value and have many health benefits. This study aims to determine the ethnobotanical aspects ethnobotanical of tea plants based on local wisdom in Ngargoyoso District, Karanganyar Regency, Central Java. This type of research is qualitative using data collection methods with surveys and interviews conducted by finding reliable informant sources. The data analysis used qualitative descriptive means. The results showed that there were 48 out of 50 people liked tea drinks, 37 people used tea plants as drinks, and 13 people used them as medicine. The level of knowledge of the Ngargoyoso people on the ethnobotany of tea plants is relatively low. The parts of the tea plant that can be used are young leaves, old leaves, young stems, and old stems.